GE_GERICHTE C/2613/2012 vom 13. Mai 2014 - GE Cour de justice (2014)
PRINCIPE DE LA TRANSPARENCE(SOCIÉTÉ); ACTION EN REVENDICATION(DROITS RÉELS); DONATION; SOCIÉTÉ SIMPLE | Cst.92.2; CO.239.1; CO.244; CO.305; CO.530